2020
DOI: 10.1002/stc.2614
|View full text |Cite
|
Sign up to set email alerts
|

Field test investigations for condition monitoring of a concrete culvert bridge using vibration responses

Abstract: Summary Over the last two decades, vibration‐based structural health and condition monitoring has gradually become one of the main methods for monitoring changes in a structure on a global scale. This method has been applied to damage detection in many areas, including aerospace, mechanical and structural systems. However, it has not been widely used for identifying condition change of the structure itself. This paper demonstrates the feasibility of utilising acceleration and strain responses measured from a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…There are several extreme value distribution models available 11,23 . If the time duration of available measurement data is short (e.g., more than 2 years but less than 20 years), the generalized Pareto distribution (also called GPD or POT) can be adopted 23 . If the time duration of available measurement data is long enough (e.g., more than 20 years), the generalized extreme value (GEV) distribution can be used 11 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There are several extreme value distribution models available 11,23 . If the time duration of available measurement data is short (e.g., more than 2 years but less than 20 years), the generalized Pareto distribution (also called GPD or POT) can be adopted 23 . If the time duration of available measurement data is long enough (e.g., more than 20 years), the generalized extreme value (GEV) distribution can be used 11 …”
Section: Discussionmentioning
confidence: 99%
“…To have a good prediction of the site‐specific extreme values, all the relevant and quality measurement data shall be included in the prediction. There are several extreme value distribution models available 11,23 . If the time duration of available measurement data is short (e.g., more than 2 years but less than 20 years), the generalized Pareto distribution (also called GPD or POT) can be adopted 23 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…He et al 7 proposed a mass-normalized mode shape identification method to enrich the mode shape resolution for bridge structures by using a parked vehicle on the bridge under environmental excitation. Lin et al 8 identified the modal frequencies of a short-span concrete bridge before and after bridge deck widening by applying frequency domain decomposition techniques to the bridge under a blocked traffic condition. Spiridonakos et al 9 proposed a method to consider the problem of parametric output-only identification of a time-varying structures based on autoregressive moving average technique to capture the varying frequencies of a laboratory scaled bridge-like structure.…”
Section: Introductionmentioning
confidence: 99%